White rot fungi in the area of DTI-Unimas test site, Unimas arboretum and timber research and technical training centre (TRTTC) - Kan, Yung Hao (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Woods become valuable resources to human nowadays due to their multiple uses. Meanwhile, most of them can be easily destroyed or bio-deteriorated by wood decay fungi. The purpose of this study was to identify the collected fungi from DTI-UNIMAS field test site, Unimas arboretum and Timber Research and Technical Training Centre (TRTTC) which were Garnoderma sp., Trametes sp., Microporus xanthopus, Lentinus conatus, Lentinus / Pleurotus sp., and Pycnoporus sanguineus. Most of the white rot fungi composed essentially of lignin peroxidase enzyme, cellulase and laccase. The clamp connection of certain fungi was identified. These respective fungi species were isolated and then underwent the examination of wood decay test on Jelutong wood based on weight loss. All fungi species were tested on agar block test (2% MEA agar). The average percentage of weight losses were obtained and calculated after five weeks. The results showed that Pynoporus sanguineus (17.14 %) had highest wood decay ability than Ganoderma sp. (15.53 %), Trametes sp. (10.55 %), Microporus xanthopus (12.60 %), Lentinus conatus (14.91 %) and Lentinus / Pleurotus sp. (15.29 %). Pcynoporus sanguineus had no significantly different with Ganoderma sp., Lentinus connatus , and Lentinus / Pleurotus sp., whereas both Trametes sp. and Microporus xanthopus showed significantly different based on weight loss.